Pengaruh Kolaborasi Terhadap Kinerja Logistik dengan Kapabilitas Logistik Sebagai Variabel Intervening - Ziyaduddin, Hammad Faher; Mukhsin, Moh; Satyanegara, Diqbal (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the effect of collaboration on logistics performance with logistics capability as an intervening variable at PT. Ciomas Ariya Samudera. Using a quantitative approach through a survey of 40 companies that use the service of PT. Ciomas Ariya Samudera, the data were analyzed using Structural Equation Modeling (SEM) method the assistance of SmartPLS 4.1.12 software. The result show that: (1) collaboration has a positive and significant effect on logistics performance, (2) collaboration has a positive and significant effect on logistics performance, (3)logistics capability has a positive and significant effect on logistics performance, (4) logistics capability has a positive and significant effect in mediating the relationship between collaboration and logistics performance.